2006
DOI: 10.1016/j.brainres.2006.04.046
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of DMT1 expression in choroidal epithelia of the blood–CSF barrier following manganese exposure in vitro

Abstract: Divalent metal transporter 1 (DMT1), whose mRNA possesses a stem-loop structure in 3′-untranslated region, has been identified in most organs and responsible for transport of various divalent metal ions. Previous work from this laboratory has shown that manganese (Mn) exposure alters the function of iron regulatory protein (IRP) and increases iron (Fe) concentrations in the cerebrospinal fluid (CSF). This study was designed to test the hypothesis that Mn treatment, by acting on protein-mRNA binding between IRP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
54
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(63 citation statements)
references
References 48 publications
(64 reference statements)
7
54
2
Order By: Relevance
“…This elevation in DMT1 expression is not region-specific; nonetheless, the data directly relate the effect of an enhanced Mn diet with augmentation in DMT1 expression (Garcia et al, 2006). In addition, this correlation is supported by in vitro data where exposure to Mn for 24 and 48 hours has been shown to increase DMT1 expression in the immortalized choroidal epithelial Z310 cell line by 45% and 78% respectively (Wang et al, 2006). …”
mentioning
confidence: 61%
“…This elevation in DMT1 expression is not region-specific; nonetheless, the data directly relate the effect of an enhanced Mn diet with augmentation in DMT1 expression (Garcia et al, 2006). In addition, this correlation is supported by in vitro data where exposure to Mn for 24 and 48 hours has been shown to increase DMT1 expression in the immortalized choroidal epithelial Z310 cell line by 45% and 78% respectively (Wang et al, 2006). …”
mentioning
confidence: 61%
“…Data showed that mRNA levels of DMT1, Mdr1b, Oat3, and OB-Ra in choroid plexus tissue were significantly higher than those in Z310 cells when cultured regularly on 6-well plate. Our previous studies have also demonstrated that Z310 cells possess both DMT-1 and TTR proteins (Zheng & Zhao, 2002;Wang, et al 2006).…”
Section: Mrna Expression Of Representative Transporters In Z310 Cellsmentioning
confidence: 79%
“…44, many transporters are expressed in the CP and are therefore discussed to contribute to Mn transport. Because DMT1 has been shown to be present in the blood-CSF barrier in several studies and Mn exposure resulted in an increased DMT1 expression in rats (52), the present study intended to assess the role of DMT1 in Mn transfer processes. However, applying the DMT1 inhibitor NSC306711, our data show that in the applied in vitro system DMT1 is not the major transporter for Mn uptake into the brain via the blood-CSF barrier.…”
Section: Discussionmentioning
confidence: 99%